2007
DOI: 10.1175/mwr3463.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Horizontal Environmental Variability on Numerically Simulated Convective Storms. Part I: Variations in Vertical Shear

Abstract: Severe convective storms are typically simulated using either an idealized, horizontally homogeneous environment (i.e., single sounding) or an inhomogeneous environment constructed using numerous types of observations. Representing opposite ends of the spectrum, the former allows for the study of storm dynamics without the complicating effects of either land surface or atmospheric variability, though arguably at the expense of physical realism, while the latter is especially useful for prediction and data sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 40 publications
(29 reference statements)
5
37
0
1
Order By: Relevance
“…The simulation also includes a background baroclinic environment (an element largely neglected by many purely idealized modeling studies of the past). This approach allows a more realistic treatment of the larger-scale environment by including an upper-level jet stream that is in thermal wind balance, and accounting for the influence of the Coriolis force on MCS evolution (important to MCS motion over extended time intervals); Skamarock et al (1994), Jewett and Wilhelmson (2006), and Richardson et al (2007) also discuss the advantages of such a framework.…”
Section: A Quasi-idealized Modeling Approachmentioning
confidence: 99%
“…The simulation also includes a background baroclinic environment (an element largely neglected by many purely idealized modeling studies of the past). This approach allows a more realistic treatment of the larger-scale environment by including an upper-level jet stream that is in thermal wind balance, and accounting for the influence of the Coriolis force on MCS evolution (important to MCS motion over extended time intervals); Skamarock et al (1994), Jewett and Wilhelmson (2006), and Richardson et al (2007) also discuss the advantages of such a framework.…”
Section: A Quasi-idealized Modeling Approachmentioning
confidence: 99%
“…While the majority of the findings discussed thus far deal with how a storm initially organizes within a particular shear environment, Richardson et al (2007) showed that variations in environmental shear during the course of a storm's lifetime may have an impact on its organization as well. Using idealized numerical simulations with horizontally varying vertical wind shear, the authors found that storms became increasingly organized as they moved into a region with stronger vertical shear.…”
Section: Introductionmentioning
confidence: 99%
“…This follows many prior supercell modeling studies that have studied the NSE in relation to the resulting storm type and behavior (e.g., Klemp and Wilhelmson 1978;Weisman and Klemp 1982). Previous observational and modeling studies have shown or suggested that nonhomogeneous features (i.e., preexisting baroclinic regions and vertical vorticity) can also influence low-level rotation and tornado potential in supercells (e.g., Maddox et al 1980;Markowski et al 1998;Atkins et al 1999;Fierro et al 2006;Richardson et al 2007). By excluding these nonhomogeneous features, the ability (or inability) of a modeled storm to produce a tornado can be limited to the NSE.…”
Section: Introductionmentioning
confidence: 53%